Causes of drop out from a physical exercise supervised program specific to older adults - Paulo Giusti Rossi; Leticia Carnaz; Wanderson Luis Bertollo; Anielle Cristhine de Medeiros Takahashi (Editora Champagnat, 2018)
Abstract Introduction: Physical exercise when performed regularly brings several health benefits, especially for older adults. However, there are barriers that induce these individuals to withdraw from exercise. Objective: This study investigated the causes of drop out from a supervised physical exercise program specific to older adults. Methods: A semi-structured questionnaire was applied by telephone contact, containing questions about their reasons for leaving the program. Demographic data were analyzed by relative and absolute frequencies, and the Chi-square test was used to verify the associations between the variables collected. A significance level of 5% was considered. Results: Fifty-nine older adults were interviewed and the main reasons for drop out were lack of time (33.9%), emergence or worsening of disease (28.8%), and the need to care for family members with health problems (18.7%). A high percentage of older adults (62.7%) showed a worsening in health status after leaving the program, with changes in muscle strength (80.0%), balance (76.7%), and motor coordination (40.0%). Conclusion: A professional intervention is suggested to enable organizational control of factors related to lack of time, as well as a logistical monitoring service for older adults and/or family members who fall ill, promoting the return to practice as soon as possible.